Radiology Safety in Iraq Exposes Critical Gaps in Training and Knowledge: Keselamatan Radiologi di Irak Mengungkap Kesenjangan Kritis dalam Pelatihan dan Pengetahuan - Ghufran Abdulsalam Razooqi; Husham Hussain Abdul Ra’aoof; Sajjad Salim Issa (Universitas Muhammadiyah Sidoarjo, 2024)
Ionizing radiation, with 18% from man-made sources, is widely used in medical imaging, posing significant hazards. This study assessed the knowledge, attitude, and practice of 125 radiology staff in Basrah, Iraq, using a cross-sectional design from February to June 2023. Data were collected via structured questionnaires and analyzed with SPSS version 26. Results showed 66.4% of respondents had good knowledge, with higher scores among males and those with higher education, particularly doctors. Positive attitudes were seen in 95.2% of participants, but correct practices varied significantly, and 88.8% had not undergone training on radiation hazards. The study underscores the need for improved training and education to enhance radiation safety awareness and practices. Highlights: Knowledge Levels: 66.4% showed good radiation hazard knowledge. Training Gaps: 88.8% lacked radiation safety training. Education Impact: Higher education, especially doctors, improved knowledge and practices. Keywords: Ionizing Radiation, Radiation Hazards, Radiology Staff, Knowledge Assessment, Safety Practices